Stability in E-convex programming - Ebrahim A. Youness (International Journal of Mathematics and Mathematical Sciences)
We define and analyze two kinds of stability in E-convex programming problem in which the feasible domain is affected by an operator E. The first kind of this stability is that the set of all operators E that make an optimal set stable while the other kind is that the set of all operators E that make certain side of the feasible domain still active.